Implementation of Short Video Digital Marketing to Increase Sustainable Tourism Visits: Study Batik Girilayu Tourist Village in Karanganyar Regency - Hasni Dyah Kurniawati; Tiara Indah; Sujatmiko Sujatmiko (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
This study aims to analyze the effectiveness of short video marketing in increasing tourist interest in visiting Batik Girilayu Tourism Village. A quantitative approach was used through an experimental design with an intervention group (short video) and a control group (posters/photos), using the Mann–Whitney test to see the differences between the groups. The test results showed significant differences in most variables, such as visual perspective, visual content, narration appeal, and travel intention, where the intervention group obtained a higher mean rank than the control group. To reinforce the quantitative results, in-depth interviews were conducted with seven respondents from the intervention and control groups, as well as representatives of the tourism village management. The interview results showed that short videos provided a more immersive, interesting, and memorable experience, making them more effective in building interest in visiting. In addition, tourism village managers assessed that short videos were easier to go viral on social media and contributed to increasing the interaction of potential tourists with the management. This study confirms that short video marketing is an effective promotional strategy in attracting tourists, although there are still limitations in the scope of the sample, the social media platforms studied, and the number of interview respondents. Therefore, further research with a broader scope, the use of various digital platforms, and long-term evaluation are needed to strengthen the findings.